The Macroeconomics of Managing Increased Aid Inflows : Experiences of Low-Income Countries and Policy Implications. (Policy Papers; Policy Paper, 2005)
Investigates the macroeconomic challenges for low-income countries created by a surge in aid inflows. It develops an analytical framework for examining possible policy responses to increased aid, and then applies this framework to the experience of five relatively well-governed countries that experienced a recent surge in aid inflows: Ethiopia, Ghana, Mozambique, Tanzania, and Uganda. Each country's policies were supported by a PRGF arrangement during most of the period under review.